ANALISIS FRAMING PEMBERITAAN FOX DAN AL JAZEERA PADA PERISTIWA TEWASNYA ENAM SANDERA ISRAEL DI GAZA PALESTINA - Nursanita; Misroji; Derysmono (STAI DI AL-HIKMAH, 2024)
This study aims to analyze the framing of news coverage by FOX and Al Jazeera regarding the deaths of six Israeli hostages in Gaza, Palestine. The conflict between Israel and Palestine erupted on October 7, 2023, with Hamas naming their operation Tofan Al Aqsha. Al Aqsha refers to the third holiest mosque in Islam, located in Palestine, following Masjid al-Haram in Mecca and Al-Masjid an-Nabawi in Medina, Saudi Arabia. Israel seized Palestinian territories through the Nakba massacre and violated UN Resolution No. 181 of 1947. Israel's prolonged oppression of Palestinians triggered resistance led by the Hamas movement. This research employs a qualitative descriptive method with Zongdang Pan and Gerald M. Kosicky's framing analysis, encompassing syntactic, script, thematic, and rhetorical elements. The findings indicate that FOX emphasizes Hamas's brutality, portraying them as terrorists and framing Israel as a party fighting for justice. Conversely, Al Jazeera highlights the suffering of Palestinians caused by Israeli policies, presenting a broader and more contextual perspective. Both media outlets frame the conflict based on their respective viewpoints and interests.